PREPARATION STUDY OF FE₃O₄-COCONUT SHELL CHARCOAL AS A CARBON QUANTUM DOTS CQDS BASED NANOPARTICLE MATERIAL - Yoshi Adhitia Mahendra; Siti Khomsatin (Jurnal Crystal : Publikasi Penelitian Kimia dan Terapannya, 2025)
This research aims to study the preparation of Fe₃O₄ nanoparticles based on coconut shell charcoal as a carbon source for Carbon Quantum Dots (CQDs) using the hydrothermal method. The synthesis of Fe₃O₄ nanoparticles was carried out through the coprecipitation method by mixing FeCl₃·6H₂O and FeSO₄·7H₂O solutions while stirring at 60°C, followed by the addition of CQD solution derived from coconut shell charcoal. The variable parameters include the mass of coconut shell charcoal, reaction temperature, and precursor concentration. Characterization was performed using X-ray Diffraction (XRD) to determine the optical properties, crystal structure, and magnetic properties of the resulting nanoparticles. The results indicate that Fe₃O₄-CQD nanoparticles possess a specific crystal structure and magnetic properties suitable for applications in bioimaging and catalysis. This research contributes to the utilization of organic waste as a raw material for environmentally friendly nanomaterials and has the potential to enhance the economic value of coconut waste. Suggestions for future development include optimization of synthesis parameters and performance testing of the material in real-world applications.